Ocupação e reconstrução do Iraque: a atuação da Coalizão de Autoridade Provisória (2003-2004) - Amaral, Rodrigo Augusto Duarte [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
Between March 2003 and June 2004, the United States of America (US), together with Britain, occupied Iraq and obtained the status of Provisional Authority granted by the UN Security Council in Resolution 1483 to rebuild the Iraqi state after the overthrow of the Baath Regime. For the first time since the end of World War II, an international power gained occupying power status through United Nations (UN), without being a UN proper mandate, as usually in peacekeeping operations governed by the international body. The 2003 invasion of Iraq had a consensus in American political though that the United States would have the responsibility and duty to overthrow Saddam's regime, which allegedly committed crimes against humanity, posed a threat to international security. To a large extent, the American formula for the invasion and occupation of Iraq consisted in justifying its actions in terms of "humanitarian reason" and legitimizing them by means of legal mechanisms. Implementation of the Iraq occupation plan had a key role for members of the Iraqi opposition elite to the Baath Regime in support of the Anglo-American powers agenda. However, if this unprecedented statebuilding process is analyzed by leaving aside these humanitarian premises, unlike the mainstream US foreign policy analysis, one can identify possible political-economic benefits that result from this reconstruction project in Iraq. Based on the analysis of the official documents of the Provisional Authority Coalition (CPA) and questioning the internationalist liberal premises that guided the justification and later criticism of the results of CPA administration, we were able to identify possible political-economic benefits to the US and its corporations during The 14 months of occupation. Particularly in the energy, agriculture, security services and infrastructure sectors, as well as other financial benefits to non-state sectors (such as NGOs and informal economies). In terms of power, the occupation resulted in the US-Iraq approaching of US dominance, and in terms of market CPA liberalized the Iraqi economy allowing multinational access to various sectors of the Iraqi market. Thus, it is evident the consolidation of an Iraqi political-economic agenda submissive to the North American interests.

Entre março de 2003 e junho de 2004, os Estados Unidos da América, em conjunto com a Grã-Bretanha, ocuparam o Iraque e obtiveram o status de Autoridade Provisória emitido pelo Conselho de Segurança da Organização das Nações Unidas (CSONU) na Resolução 1483 para reconstruir o Estado iraquiano após a derrubada do Regime Baath. Pela primeira vez desde o final da segunda Guerra Mundial, uma potência ganhava status de força ocupante pela Organização das Nações Unidas (ONU), sem ser um mandato da ONU propriamente, como usualmente nas operações de paz (Peacekeeping operations) regidas pelo órgão internacional. A invasão do Iraque em 2003, contou com um consenso no pensamento político norteamericano no qual os EUA teriam a responsabilidade e o dever de derrubar o regime de Saddam Hussein, que supostamente cometia crimes contra humanidade, representava uma ameaça à segurança internacional. Em grande medida, a fórmula norte-americana para a invasão e ocupação do Iraque consistiu em justificar suas ações em termos de “razão humanitária” e legitimá-las por meio de mecanismos jurídicos. A execução do plano de ocupação do Iraque contou com um papel fundamental de membros da elite iraquiana da oposição ao Regime Baath em apoio a agenda das potências anglo-americanas. Entretanto, se esse inédito processo de statebuilding for analisado deixando de lado essas premissas humanitárias, ao contrário do que fazem as análises mainstream de política externa dos EUA, pode-se identificar possíveis benefícios político-econômicos consequentes a esse projeto de reconstrução do Iraque. A partir da análise dos documentos oficiais da Coalizão de Autoridade Provisória (CAP) e o questionamento às premissas liberais internacionalistas que pautaram a justificativa e posteriormente as críticas aos resultados da administração da CAP, pudemos identificar possíveis benefícios político-econômicos aos EUA e suas corporações durante os 14 meses de ocupação. Sobretudo nos setores de energia, agricultura, serviços de segurança e infraestrutura, e ainda outros benefícios financeiros a setores não-estatais (como das Organizações não Governamentais e as economias informais). Em termos de poder, a ocupação resultou na aproximação entre EUA e Iraque de domínio norte-americano, e em termos de mercado a CAP liberalizou a economia iraquiana permitindo acesso de multinacionais a diversos setores do mercado iraquiano. Assim, evidencia-se a consolidação de uma agenda político-econômica iraquiana submissa aos interesses norte-americanos.
Occupation and reconstruction of Iraq: the Coalition of Provisional Authority performance (2003-2004)
Keywords: Ocupação; Reconstrução; Iraque; Coalizão de autoridade provisória; Resolução 1483 do CSONU; Agenda político-econômica dos EUA; Occupation; Reconstruction; Coalition of provisional authority; UN Security Council Resolution 1483; US political-economic agenda